(untitled) (Eurasian Journal of Engineering and Technology, 2023)
Based on the basic properties of alfalfa seeds, the article substantiates the constructive scheme of their cleaning from seeds of quarantine plants. For sorting and cleaning of alfalfa seeds the constructive scheme consisting of concentric cylindrical electrodes with increasing intensity of electric field in the direction of seed movement has been adopted.